value of theta will be?
Attachments:
![](https://hi-static.z-dn.net/files/d0a/45b06b45d8822ab582099543970037b6.jpg)
Answers
Answered by
0
we know that sin theta is equal to sin theta by 2 cos theta by 2
Therefore
U is equal to 2 cos theta by 2
Cos inverse u/2=theta by 2
theta equal to 2 Cos inverse u by 2
Therefore
U is equal to 2 cos theta by 2
Cos inverse u/2=theta by 2
theta equal to 2 Cos inverse u by 2
shruti327:
yes the answer will be in terms of u
Answered by
7
We will use the identity:
![\boxed{\sin \theta = 2\, \sin \frac{\theta}{2} \, \cos\frac{\theta}{2}} \boxed{\sin \theta = 2\, \sin \frac{\theta}{2} \, \cos\frac{\theta}{2}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Csin+%5Ctheta+%3D+2%5C%2C+%5Csin+%5Cfrac%7B%5Ctheta%7D%7B2%7D+%5C%2C+%5Ccos%5Cfrac%7B%5Ctheta%7D%7B2%7D%7D)
Now, we can solve as follows:
![u \times \sin \frac{\theta}{2} = \sin \theta \times 1 \\ \\ \\ \implies u \sin \frac{\theta}{2} = 2\sin \frac{\theta}{2}\cos \frac{\theta}{2} \\ \\ \\ \implies2\sin \frac{\theta}{2} \cos \frac{\theta}{2} - u \sin \frac{\theta}{2} =0 \\ \\ \\ \implies \sin \frac{\theta}{2} \left( 2\cos \frac{\theta}{2} -u \right) = 0 \\ \\ \\ \implies \sin \frac{\theta}{2} = 0 \quad OR \quad 2\cos \frac{\theta}{2} - u = 0 \\ \\ \\ \implies \frac{\theta}{2} = 0 \quad OR \quad \cos \frac{\theta}{2} = \frac{u}{2} u \times \sin \frac{\theta}{2} = \sin \theta \times 1 \\ \\ \\ \implies u \sin \frac{\theta}{2} = 2\sin \frac{\theta}{2}\cos \frac{\theta}{2} \\ \\ \\ \implies2\sin \frac{\theta}{2} \cos \frac{\theta}{2} - u \sin \frac{\theta}{2} =0 \\ \\ \\ \implies \sin \frac{\theta}{2} \left( 2\cos \frac{\theta}{2} -u \right) = 0 \\ \\ \\ \implies \sin \frac{\theta}{2} = 0 \quad OR \quad 2\cos \frac{\theta}{2} - u = 0 \\ \\ \\ \implies \frac{\theta}{2} = 0 \quad OR \quad \cos \frac{\theta}{2} = \frac{u}{2}](https://tex.z-dn.net/?f=u+%5Ctimes+%5Csin+%5Cfrac%7B%5Ctheta%7D%7B2%7D+%3D+%5Csin+%5Ctheta+%5Ctimes+1+%5C%5C+%5C%5C+%5C%5C+%5Cimplies+u+%5Csin+%5Cfrac%7B%5Ctheta%7D%7B2%7D+%3D+2%5Csin+%5Cfrac%7B%5Ctheta%7D%7B2%7D%5Ccos+%5Cfrac%7B%5Ctheta%7D%7B2%7D+%5C%5C+%5C%5C+%5C%5C+%5Cimplies2%5Csin+%5Cfrac%7B%5Ctheta%7D%7B2%7D+%5Ccos+%5Cfrac%7B%5Ctheta%7D%7B2%7D+-+u+%5Csin+%5Cfrac%7B%5Ctheta%7D%7B2%7D+%3D0+%5C%5C+%5C%5C+%5C%5C+%5Cimplies+%5Csin+%5Cfrac%7B%5Ctheta%7D%7B2%7D+%5Cleft%28+2%5Ccos+%5Cfrac%7B%5Ctheta%7D%7B2%7D+-u+%5Cright%29+%3D+0+%5C%5C+%5C%5C+%5C%5C+%5Cimplies+%5Csin+%5Cfrac%7B%5Ctheta%7D%7B2%7D+%3D+0+%5Cquad+OR+%5Cquad+2%5Ccos+%5Cfrac%7B%5Ctheta%7D%7B2%7D+-+u+%3D+0+%5C%5C+%5C%5C+%5C%5C+%5Cimplies+%5Cfrac%7B%5Ctheta%7D%7B2%7D+%3D+0+%5Cquad+OR+%5Cquad+%5Ccos+%5Cfrac%7B%5Ctheta%7D%7B2%7D+%3D+%5Cfrac%7Bu%7D%7B2%7D)
![\implies \theta = 0 \quad OR \quad \frac{\theta}{2} = \cos^{-1} \frac{u}{2} \\ \\ \\ \impies \boxed{\theta=0} \quad OR \quad \boxed{\theta = 2\cos^{-1}\frac{u}{2}} \implies \theta = 0 \quad OR \quad \frac{\theta}{2} = \cos^{-1} \frac{u}{2} \\ \\ \\ \impies \boxed{\theta=0} \quad OR \quad \boxed{\theta = 2\cos^{-1}\frac{u}{2}}](https://tex.z-dn.net/?f=%5Cimplies+%5Ctheta+%3D+0+%5Cquad+OR+%5Cquad+%5Cfrac%7B%5Ctheta%7D%7B2%7D+%3D+%5Ccos%5E%7B-1%7D+%5Cfrac%7Bu%7D%7B2%7D+%5C%5C+%5C%5C+%5C%5C+%5Cimpies+%5Cboxed%7B%5Ctheta%3D0%7D+%5Cquad+OR+%5Cquad+%5Cboxed%7B%5Ctheta+%3D+2%5Ccos%5E%7B-1%7D%5Cfrac%7Bu%7D%7B2%7D%7D)
Thus, the value of
can be
or ![2\cos^{-1}\frac{u}{2} 2\cos^{-1}\frac{u}{2}](https://tex.z-dn.net/?f=2%5Ccos%5E%7B-1%7D%5Cfrac%7Bu%7D%7B2%7D)
Now, we can solve as follows:
Thus, the value of
Similar questions